2009
DOI: 10.33549/physiolres.931390
|View full text |Cite
|
Sign up to set email alerts
|

Transient hypertension and sustained tachycardia in mice housed individually in metabolism cages

Abstract: The novel environment of a metabolic cage can be stressful for rodents, but few studies have attempted to quantify this stressresponse. Therefore, we determined the effects on mean arterial pressure (MAP) and heart rate (HR), of placing mice of both sexes in metabolism cages for 2 days. After surgical implantation of a carotid artery catheter mice recovered individually in standard cages for 5 days. Mice then spent 2 days in metabolism cages. MAP and HR were monitored in the standard cage on Day 5 and in metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…This effect has been shown in mice on a mixed C57BL/6 J/129/sv background, but in these mice, MAP did return to baseline following day 1 in the metabolic cages, with HR remaining elevated. 34 HR remained elevated in our study, and there was a significant interaction between time and genotype in the metabolic cages. Cosinor analysis was carried out on this dataset and showed that the robustness of HR (strength of the rhythm) was only ∼ 20% for both genotypes.…”
Section: Discussionsupporting
confidence: 53%
“…This effect has been shown in mice on a mixed C57BL/6 J/129/sv background, but in these mice, MAP did return to baseline following day 1 in the metabolic cages, with HR remaining elevated. 34 HR remained elevated in our study, and there was a significant interaction between time and genotype in the metabolic cages. Cosinor analysis was carried out on this dataset and showed that the robustness of HR (strength of the rhythm) was only ∼ 20% for both genotypes.…”
Section: Discussionsupporting
confidence: 53%
“…Hydrophobic sand could be used for urine collection in the control cage and to investigate whether this is a useful alternative to metabolic cage restraint for mice, as it was already described for rats [ 39 , 40 ]. To collect more data as part of metabolic phenotyping, the mean arterial pressure and heart rate of mice restrained in different metabolic cage types could be assessed [ 11 ]. Since implantation of a carotid artery catheter is required for this measurement, including anesthesia and surgery before the start of the experiment, we left this quite interesting measurement aside in the sense of the refinement guiding principle.…”
Section: Discussionmentioning
confidence: 99%
“…The energy expenditure of mice may be elevated particularly during metabolic cage housing at 20–22 °C due to the absence of conspecifics and nesting material as mice are deprived of the possibility of keeping themselves warm through huddling and nests [ 9 , 10 ]. The heat of mice is additionally dissipated from the paws via the metal grid [ 11 , 12 ]. To investigate potential cold stress during metabolic cage restraint, thermal images of mice housed in these cage systems may be taken.…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies studied MC housing of mice showing that mice housed in MCs had an increased BP for several hours and prolonged tachycardia las)ng for two days 24 and sugges)ng that MC housing accelerates metabolism 16,[25][26][27] and oxida)ve stress 16 . While some studies showed that mice had stable urina)on rates in the MC aRer 3-4 days 28 , others stated that mice did not acclima)ze 24,25,29 , even aRer three weeks 16 . Acclima)sa)on was paralleled by an increase in food/water intake and urinary output 28,30 .…”
Section: Introduc#onmentioning
confidence: 99%
“…MCs are kept at standard housing condi)ons (ambient temperature of 23°C). However, it remains widely unclear to what extent ambient temperature contributes as a major stressor 16,[24][25][26][27][28][29][30] while a recent study demonstrated a beneficial effect of thermoneutral temperature on some metabolic parameters 27 . To the best of our knowledge, only one study measured body temperatures in mice during MC housing, showing an average body surface temperature of around 30°C at an ambient cage temperature of 22.5°C 25 .…”
Section: Introduc#onmentioning
confidence: 99%